2009
DOI: 10.1002/gcc.20722
|View full text |Cite
|
Sign up to set email alerts
|

SUZ12 is a candidate target of the non‐canonical WNT pathway in the progression of chronic myeloid leukemia

Abstract: Polycomb proteins form multiprotein complexes that repress target genes by chromatin remodeling. In this work, we report that the SUZ12 polycomb gene is over-expressed in bone marrow samples of patients at the blastic phase of chronic myeloid leukemia. We also found a direct interaction between polycomb group genes and the WNT signaling pathway in chronic myeloid leukemia transformation. Electrophoretic mobility shift assay (EMSA), Chromatin immunoprecipitation assay (ChIP), and mass spectrometry assays identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…Besides, the present research has shown that knock-down of Suz12 by small interfering RNA (siRNA) produces a significant decrease of 98% in the expression of Kaiso in K562 cells, the first established human immortalized myelogenous leukemia line [13]. Evidence presented above suggests that, at least, The genes Wnt11 and Wnt5a up-regulate Suz12 expression (supressor of zeste 12) acting in the nucleus as transcriptional factors, as described previously by [15]. (b) Suz12 activates the transcription of Kaiso, as described here in this article and (c) Kaiso and TCF/LEF cooperate to repress the transcription of Wnt11 as described by [14].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Besides, the present research has shown that knock-down of Suz12 by small interfering RNA (siRNA) produces a significant decrease of 98% in the expression of Kaiso in K562 cells, the first established human immortalized myelogenous leukemia line [13]. Evidence presented above suggests that, at least, The genes Wnt11 and Wnt5a up-regulate Suz12 expression (supressor of zeste 12) acting in the nucleus as transcriptional factors, as described previously by [15]. (b) Suz12 activates the transcription of Kaiso, as described here in this article and (c) Kaiso and TCF/LEF cooperate to repress the transcription of Wnt11 as described by [14].…”
Section: Discussionsupporting
confidence: 76%
“…Previously Pizzatti et al, reported that both Wnt5a and Wnt11 upregulate the expression of Suz12 by acting as transcription factors in the cell nucleus [15] (Figure 2a). The real importance of that positive regulation should be understood in the context of leukemia patients who present, in the blast phase, a significant increase in the expression of Suz12.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations